Tingkat Kemandirian Aktivitas Lansia Tua Pria di UPT Pelayanan Sosial Lanjut Usia Binjai - Bagus Prabudi; Sapta Dewanti (Jurnal Riset Hesti Medan, 2022)
Elderly is a phase of decreased intellectual and physical abilities, which begins with several changes in life, a period when the organism has reached maturity in size and function and has also shown decline over time. Independence is freedom to act, not dependent to other people, not affected by other people and free to regulate oneself or one's activities both individually and in groups from various health or disease. Independent is also said to care for oneself and can carry out activities of daily life (AKS). ACC is divided into 2, namely: standard ACC and instrumental ACC. Standard AKS includes self-care skills such as eating, dressing, defecating/urinating, and bathing. Meanwhile, instrumental AKS includes complex activities such as cooking, washing, using the telephone, and using money. The purpose of this study was to determine the level of activity independence of the elderly at UPT. Binjai Elderly Social Service. Which includes activities of daily life in the elderly, the method used is a type of "descriptive qualitative" which describes the actual situation with a sample of 31 people by means of sampling "total sampling", namely determining the sample by taking the entire population. The results of this observation indicate that the majority of elderly who are independent are (61.01%), and dependent elderly are as much as (38.98%).